2020
DOI: 10.1371/journal.pone.0230633
|View full text |Cite
|
Sign up to set email alerts
|

The lectin ArtinM activates RBL-2H3 mast cells without inducing degranulation

Abstract: Mast cells are connective tissue resident cells with morphological and functional characteristics that contribute to their role in allergic and inflammatory processes, host defense and maintenance of tissue homeostasis. Mast cell activation results in the release of pro-inflammatory mediators which are largely responsible for the physiological functions of mast cells. The lectin ArtinM, extracted from Artocarpus heterophyllus (jackfruit), binds to D-manose, thus inducing degranulation of mast cells. ArtinM has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…12 RBL-2H3 cells are mucosal mast cells that have been widely used for studies of degranulation. 41,42 Presently, we found that sodium sulfite dose-dependent induced histamine and β-Hexosaminidase release, which could be inhibited by NAC and MCC950. Another research has shown that sodium sulfite induced degranulation of RBL- 2H3 cells and oxidant stress, which is consistent with our results.…”
Section: ■ Discussionmentioning
confidence: 82%
“…12 RBL-2H3 cells are mucosal mast cells that have been widely used for studies of degranulation. 41,42 Presently, we found that sodium sulfite dose-dependent induced histamine and β-Hexosaminidase release, which could be inhibited by NAC and MCC950. Another research has shown that sodium sulfite induced degranulation of RBL- 2H3 cells and oxidant stress, which is consistent with our results.…”
Section: ■ Discussionmentioning
confidence: 82%
“…Thus, a proper wound dressing should possess a highly porous structure, desired degradation rate, and minimal cytotoxicity effect besides high biocompatibility to reduce immunogenicity 6,7 . Meanwhile, there are various marketed wound care products to use in clinical application, effective wound treatment to recover skin function following chronic and severe skin damage still needs serious medical interventions, thus, a proper wound dressing is highly important to design to induce neovascular genesis and neocollagenesis besides restoration of skin integrity and function 8,9 .…”
mentioning
confidence: 99%